Pengaruh Indeks Gini Rasio, Indeks Kemahalan Konstruksi, Pengeluaran PerkapitaTerhadap Indeks Pembangunan Manusia (IPM) - Angkat, Susi Susanti; Saharuddin, Saharuddin (LPPM UNIMAL, 2023)
In recent years, the persistent issue of economic inequality, represented by the Gini Ratio, has garnered significant attention. This research explores the nuanced relationship between Gini Ratio and HDI, shedding light on how disparities in income distribution impact human development outcomes. The findings of this research have profound implications for policymakers and stakeholders. Understanding the intricate connections between economic inequality, infrastructure development, and individual spending habits can inform targeted policy interventions. By addressing these underlying factors, governments can design more effective strategies to enhance HDI, uplift marginalized communities, and foster sustainable socio-economic development. This comprehensive analysis contributes significantly to the existing body of knowledge, providing a nuanced understanding of the multifaceted factors shaping human development. As nations strive for progress, this research serves as a valuable resource, guiding policymakers toward evidence-based decisions that prioritize the well-being and prosperity of their citizens.